KAJIAN SPASIAL PARIWISATA DI ZONA RAWAN BENCANA ALAM: IMPLIKASI BAGI STRATEGI PARIWISATA BERKELANJUTAN DI KABUPATEN BIMA - Rois Dinan; MH Nateq Nouri; Vinny Corylitha Sarapang; Khairi Ahza Hail keliwar (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2026)
Tourism is increasingly recognized as a key driver of sustainable development, particularly in developing countries such as Indonesia. Beyond its contribution to Gross Domestic Product (GDP), tourism plays a strategic role in job creation, regional equity, and cultural preservation. However, in disaster-prone regions like Bima Regency, West Nusa Tenggara, tourism development faces significant challenges due to high vulnerability to natural hazards including floods, landslides, earthquakes, and tsunamis. This study employs a spatial assessment approach to identify the overlap between designated tourism areas in the Regional Spatial Plan (RTRW) and disaster-prone zones. The findings highlight the paradox between efforts to maximize tourism potential and the risks of disaster vulnerability. Spatial analysis not only identifies destinations at risk but also provides insights into the interconnections among infrastructure, community preparedness, and destination management. The study emphasizes that sustainable tourism development in disaster-prone areas can only be achieved through integrated strategies of mitigation, adaptation, and preparedness. Such approaches ensure tourist safety, strengthen local community resilience, and maintain long-term investment confidence. The objectives of this research are threefold: (1) to identify tourism subdistricts located in disaster-prone zones, (2) to analyze the implications of these vulnerabilities on tourism sustainability, and (3) to propose adaptive strategies for resilient tourism development. The results are expected to contribute to comprehensive policy directions that integrate spatial planning, disaster risk management, and sustainability strategies for building resilient tourism in Bima Regency.